Suicidality and Self-Harming Behaviors in Patients with Prader-Willi Syndrome (PWS): Case Report and Literature Review - Val Bellman; Zargham Abbass; Ramsa Sohail; Syed Jafri (Case Reports in Psychiatry)
Prader-Willi syndrome (PWS) is a rare neurodevelopmental disorder which is often associated with significant behavioral challenges and poor intellectual functioning. Research has shown that individuals with PWS are more likely to experience mental health problems, have higher relapse rates, and are at risk of self-harming behavior. Although PWS is associated with mild intellectual disability, which in itself confers a higher mortality rate, suicidality in this population is so far unreported in the literature. We present the case of an 18-year-old male patient who was admitted to our facility following exogenous insulin administration with suicidal intent. The main clinical characteristics, self-harming behaviors, and suicide risk factors of patients with PWS are discussed in this report. The article’s objective is to redirect clinicians’ attention to carefully screen and treat the underlying behavioral problems in PWS patients.